High levels of sarcospan are well tolerated and act as a sarcolemmal stabilizer to address skeletal muscle and pulmonary dysfunction in DMD. (24th October 2016) - Gibbs, Elizabeth M.; Marshall, Jamie L.; Ma, Eva; Nguyen, Thien M.; Hong, Grace; Lam, Jessica S.; Spencer, Melissa J.; Crosbie-Watson, Rachelle H.
Abstract: Duchenne muscular dystrophy (DMD) is a genetic disorder that causes progressive muscle weakness, ultimately leading to early mortality in affected teenagers and young adults. Previous work from our lab has shown that a small transmembrane protein called sarcospan (SSPN) can enhance the recruitment of adhesion complex proteins to the cell surface. When human SSPN is expressed at three-fold levels in mdx mice, this increase in adhesion complex abundance improves muscle membrane stability, preventing many of the histopathological changes associated with DMD. However, expressing higher levels of human SSPN (ten-fold transgenic expression) causes a severe degenerative muscle phenotype in wild-type mice. Since SSPN-mediated stabilization of the sarcolemma represents a promising therapeutic strategy in DMD, it is important to determine whether SSPN can be introduced at high levels without toxicity. Here, we show that mouse SSPN (mSSPN) can be overexpressed at 30-fold levels in wild-type mice with no deleterious effects. In mdx mice, mSSPN overexpression improves dystrophic pathology and sarcolemmal stability. We show that these mice exhibit increased resistance to eccentric contraction-induced damage and reduced fatigue following exercise. mSSPN overexpression improved pulmonary function and reduced dystrophic histopathology in the diaphragm. Together, these results demonstrate that SSPN overexpression is well tolerated in mdx mice and improves sarcolemma defects that underlie skeletal muscle and pulmonary dysfunction in DMD.